Firm supervisory board during pandemic: Are they still trusted? - Satrio, Arif Budi; Kontesa, Maria (Linguistics and Culture Review, 2021)
This study investigates public trust in the firm supervisory board, an essential indicator of good corporate governance in some literature. By using 474 non-financial entities in Indonesia during the COVID-19 pandemic and considering a number of firm fundamental factors, this study documents evidence of irrational investor behavior during the pandemic. Investors seem to panic and respond negatively to financial information. However, the public still believes in the independent supervisory board’s contribution to the firm. This effect is getting stronger with the presence of an increasingly dominant supervisory board. These results are still robust during repeated testing. This empirical evidence is useful to regulators in emerging markets, industry, and academia.